The impact of patient-centred versus didactic education programmes in chronic patients by severity: the case of type 2 diabetes mellitus - Windrum, Paul; Garcia-Goni, Manuel; Coad, Holly (Elsevier, 2016)
Objectives Education leads to better health-related decisions and protective behaviours. Patient self-management education programmes have been shown to be beneficial for patients with different chronic conditions, and to have a higher impact on health outcomes than didactic education. However, prior studies have not examined whether the initial severity of the condition is a factor affecting the relative impact of patients attending self-management and didactic education programmes. Methods We investigate improvements in glycemic control (measured by HbA1c) on a comparative trial on type 2 diabetes mellitus patients. Our comparative trial involves one group of type 2 diabetes patients receiving patient-centred education and another receiving didactic education. We deal with selection bias issues, estimate the different impact of both programmes and validate our analyiss using quantile regression techniques. Results We find evidence of better mean glycemic control in patients receiving the patient-centred programme, which engages better patients compared to the didactic programme. However, that differential impact is non-monotonic. Patients initially at the healthy range and who receive the patient-centred programme maintain better their condition. Patients who are close to, but not within, the healthy glycemic range benefit equally from attending either programme. Patients with very high glycemic level benefit significantly more from attending the patient-centred programme. Finally, patients with the worst initial glycemic control (far from the health range) improve equally their diabetes condition, regardless of which programme they attended. Conclusions Different patients are sensitive to different categories of education programmes. The optimal, cost effective design of preventative programmes for chronics needs to account for the different impact in different ‘patient categories’. That implies that stratifying patients and providing the appropriate preventative education programme, or looking for alternative policy implementations for unresponsive patients who have the most severe condition and are most costly.